Dual Banking System Stability Index in the Shadow of COVID-19 Pandemic - Yunita, Patria (International Journal of Islamic Economics and Finance (IJIEF), 2022)
The financial system is categorized as stable if there is no excessive volatility from financial pressures or crises. The IMF indicates that the crisis is not only related to one element but more than two or three elements of the crisis. The banking system's stability is measured by the banking stability index, gauging the effectiveness of monetary policy and financial risk. This study aims to measure the stability of the Indonesian banking system in the dual banking system model. The indicator to measure banking stability used the Z-score statistic based on fluctuations of Return on Assets for each type of bank. The Markov Switching Vector Autoregressive (MSVAR) model method was used to analyze the volatility of banking stability. Independent variables used included credit risk (NPL), Loan to Deposit Ratio, Liquidity Risk, Net Interest Margin, Capital Adequacy Ratio, Money Market Rate, Inflation, Gross Domestic Product, Federal Reserve rate, and Exchange Rate. The results of the regime switch analysis concluded that Indonesia's banking stability experienced a structural break due to the effects of the pandemic in April 2020. Based on the average Z-score value, the Islamic banking stability index was higher than conventional banking. In other words, Islamic banking was more stable than the conventional banking system. The Islamic banking stability index (iZscore) was significantly influenced by the level of Net Operating Margin, Financing to deposit ratio, Potential Loss Profit Sharing, Islamic Money Market Rate, and Exchange Rate. However, non-performing financing did not affect Islamic banking stability since the profit-sharing system implemented by Islamic banking stability was more influenced by the ratio of potential loss and profit-sharing system.